2022
DOI: 10.3390/covid2030029
|View full text |Cite
|
Sign up to set email alerts
|

Nonself Mutations in the Spike Protein Suggest an Increase in the Antigenicity and a Decrease in the Virulence of the Omicron Variant of SARS-CoV-2

Abstract: Despite extensive worldwide vaccination, the current COVID-19 pandemic caused by SARS-CoV-2 continues. The Omicron variant is a recently emerged variant of concern and is now overtaking the Delta variant. To characterize the potential antigenicity of the Omicron variant, we examined the distributions of SARS-CoV-2 nonself mutations (in reference to the human proteome) as five amino acid stretches of short constituent sequences (SCSs) in the Omicron and Delta proteomes. The number of nonself SCSs did not differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…While this is a positive aspect, a reasonably high rate of transmission could quickly exhaust existing healthcare ability, resulting in more deaths than predicted. Such healthcare stress may also lead to an increase in mortalities that are not linked to COVID‐19 62 . Omicron multiplies 70 times faster in tissues that line airway passages than the earlier Delta variant, potentially facilitating person‐to‐person spread, according to the researchers.…”
Section: Disease Severitymentioning
confidence: 99%
“…While this is a positive aspect, a reasonably high rate of transmission could quickly exhaust existing healthcare ability, resulting in more deaths than predicted. Such healthcare stress may also lead to an increase in mortalities that are not linked to COVID‐19 62 . Omicron multiplies 70 times faster in tissues that line airway passages than the earlier Delta variant, potentially facilitating person‐to‐person spread, according to the researchers.…”
Section: Disease Severitymentioning
confidence: 99%
“…It was recently found that despite its greater infectivity and transmissibility, the Omicron variant has evolved to have higher antigenicity and decreased pathogenicity in humans. This was determined by the low number of nonself stretches of short constituent sequences (NSC) in both the Omicron and Delta proteomes; however, the number of NSCs was much higher in the RBD of the Omicron spike sequence than in the Delta spike sequence [ 26 ]. These NSCs assist in identifying and escaping the immune response.…”
Section: Resultsmentioning
confidence: 99%
“…This book discussed different mathematical analyses of infectious diseases, especially regarding COVID-19. Another significant work was completed by Otaki et al [ 36 ]. They checked the distributions of SARS-CoV-2 non-self-mutation in the Omicron and Delta variants.…”
Section: Related Workmentioning
confidence: 99%